PENERAPAN PROJECT BASED LEARNING (PJBL) DENGAN PENDEKATAN LINGKUNGAN PADA MATERI FLUIDA STATIS - Gloria Loindong; Tineke Makahinda; Satyano Mongan (Charm Sains: Jurnal Pendidikan Fisika, 2023)
The project-based learning (PjBL) model with an environmental approach is a learning model that uses projects as a learning method and utilizes the environment as a learning resource. The purpose of this study was to determine the application of project-based learning (PjBL) with an environmental approach to static fluid material. The method used in this research is pre-experiment research with one group pretest-posttest design. This research was carried out through three stages. The first stage is to give a pretest to measure students' initial abilities. The second stage is to provide treatment, namely project-based learning with an environmental approach. And in the third stage, giving a posttest as an evaluation.. The subjects of this study were 11th grade students of SMA Negeri 2 Tondano in the 2022/2023 school year. After obtaining the research data, then processed with the help of SPSS 22.0 for windows to test the results of data analysis, normality test, hypothesis test and N-Gain test. The average pretest result was 59.25 and posttest result was 85.50. Based on the acquisition of N-Gain values from each student, there is an increase in the N-Gain category score with an average N-Gain value of 0.63 . The results of this study indicate that the application of project-based learning (PjBL) with an environmental approach can improve student learning outcomes in static fluid material.